Factors for Duplication of Medical Record Numbers at UPT Puskesmas Pasar Merah - Simanjuntak, Marta; Lubis, Siti Permata Sari; Simanjuntak, Esraida; Hutasoit, Theresia (CV. Devitara, 2024)
Duplication of medical record numbers is a problem that often occurs in the Integrated Service Unit (UPT) of the Pasar Merah Health Center. This study aims to identify the factors that cause duplication of medical record numbers at UPT Puskesmas Pasar Merah. This research method uses a qualitative approach with in-depth interviews with medical administration officers, patient registration officers, and medical personnel directly involved in managing medical record numbers. In addition, observations were also made to understand the process of managing medical record numbers at UPT Puskesmas Pasar Merah.The results showed that the factors of duplication of medical record numbers involved several aspects, including lack of training of medical administrative officers in database management, recording systems that were not effectively integrated between service units, and the unavailability of medical record number validation when registering new patients. In addition, human error factors such as writing and recording errors are also the cause of duplication of medical record numbers. The recommendations of this study include improving training for medical administrative officers in database management, developing an integrated recording system, implementing direct validation of medical record numbers during patient registration, and strengthening supervision mechanisms to prevent human error in managing medical record numbers. This research is expected to contribute to the improvement of the medical record management system at UPT Puskesmas Pasar Merah, so as to reduce the incidence of duplication of medical record numbers and increase efficiency and accuracy in managing patient data.